Brain cortical alterations in COVID-19 patients with neurological symptoms - Sanabria-Diaz, Gretel; Etter, Manina Maja; Melie-Garcia, Lester; Lieb, Johanna M.; Psychogios, Marios-Nikos; Hutter, Gregor; Granziera, Cristina (Frontiers in Neuroscience, 2022)
Background: Growing evidence suggests that the central nervous system is affected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) since infected patients suffer from acute and long-term neurological sequelae. Nevertheless, it is currently unknown whether the virus affects the brain cortex. The purpose of this study was to assess the cortical gray matter volume, the cortical thickness, and the cortical surface area in a group of SARS-CoV-2 infected patients with neurological symptoms compared to healthy control subjects. Additionally, we analyzed the cortical features and the association with inflammatory biomarkers in the cerebrospinal fluid (CSF) and plasma. Method: Thirty-three patients were selected from a prospective cross-sectional study cohort during the ongoing pandemic (August 2020-April 2021) at the university hospitals of Basel and Zurich (Switzerland). The group included patients with different neurological symptom severity (Class I: nearly asymptomatic/mild symptoms, II: moderate symptoms, III: severe symptoms). Thirty-three healthy age and sex-matched subjects that underwent the same MRI protocol served as controls. For each anatomical T1w MPRAGE image, regional cortical gray matter volume, thickness, and surface area were computed with FreeSurfer. Using a linear regression model, cortical measures were compared between groups (patients versus controls; Class I versus II-III), with age, sex, MRI magnetic field strength, and total intracranial volume/mean thickness/total surface area as covariates. In a subgroup of patients, the association between cortical features and clinical parameters was assessed using partial correlation adjusting for the same covariates. P-values were corrected using a false discovery rate (FDR). Results: Our findings revealed a lower cortical volume in COVID-19 patients’ orbitofrontal, frontal, and cingulate regions than in controls (p < 0.05). Regional gray matter volume and thickness decreases were negatively associated with CSF total protein levels, the CSF/blood-albumin ratio, and CSF EN-RAGE levels. Conclusion: Our data suggest that viral-triggered inflammation leads to neurotoxic damage in some cortical areas during the acute phase of a COVID-19 infection in patients with neurological symptoms.